CMT Welding of Titanium and Stainless Steel Using CuSi3 Electrode - Poláková, Nela; Dostál, Petr (Mendelova univerzita v Brně, 2019)
The article deals with the possibility of a tight permanent joint of X5CrNi 18-10 austenitic steel and UNS N50400 titanium. The nuclear and chemical industries are in particular interested in solving this problem. The joining by means of fusion welding has come up against unreliability due to the formation of brittle intermetallic compounds between titanium and iron. The article deals with joining of these two heterogeneous materials by an innovative CMT welding method. CuSi3 soldering electrode was chosen as the additional material. Protective atmosphere consisting of clean argon has been chosen due to the undesirable gas absorption by titanium at temperatures over 600 oC. The results will compare different welding parameters and their impact on the quality of the weld joint. The quality of the created welds will be verified on the basis of the tensile test and the results will be graphically visualized. The microhardness in the weld and its surroundings will be measured. The microhardness measurement results will be graphically displayed. The experimental results will be supplemented by macrostructure snapshots and metallographic analysis snapshots.
Keywords: soldering; weldment; argon; joint; tensile strength